2006
DOI: 10.1021/bc0502816
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Carbohydrate-Based HIV-1 Vaccine:  Synthesis and Immunological Studies of Oligomannose-Containing Glycoconjugates

Abstract: Human antibody 2G12 is a broadly neutralizing antibody that exerts its anti-HIV activity by targeting a novel oligomannose cluster on HIV-1 gp120. It was previously demonstrated that synthetic oligomannose clusters could mimic the carbohydrate epitope of 2G12 and showed enhanced antigenicity (Wang L. X. et al. (2004) Chem.Biol. 11, 127). This paper describes the synthesis of oligomannose-containing glycoconjugates that include either a carrier protein or a universal T-helper epitope peptide to provide an effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
114
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(118 citation statements)
references
References 40 publications
4
114
0
Order By: Relevance
“…Inability to induce a response to the oligomannan is not the reason for this failure because we clearly show that the conjugate elicited a robust carbohydrate-specific antibody response. Our results corroborate recently published work (19) in which synthetic oligomannans were coupled to a variety of carriers and tested as potential vaccine candidates. Although in this study no attempt was made to mimic the proposed epitope structure, the conjugates showed some ability to bind 2G12.…”
Section: 00e+04supporting
confidence: 90%
See 1 more Smart Citation
“…Inability to induce a response to the oligomannan is not the reason for this failure because we clearly show that the conjugate elicited a robust carbohydrate-specific antibody response. Our results corroborate recently published work (19) in which synthetic oligomannans were coupled to a variety of carriers and tested as potential vaccine candidates. Although in this study no attempt was made to mimic the proposed epitope structure, the conjugates showed some ability to bind 2G12.…”
Section: 00e+04supporting
confidence: 90%
“…Crystallographic studies of Fab 2G12 bound to a Man 9 GlcNAc 2 oligosaccharide revealed a unique interlocked V H domain-swapped dimer, which presents an extended high-affinity binding surface optimized for interaction with clustered carbohydrates (13). Although several reports have confirmed the critical role of a Man␣1-2Man disaccharide in the 2G12 epitope, the optimal form of a synthetic carbohydrate mimetic of the epitope remains undefined (14)(15)(16)(17)(18)(19).…”
mentioning
confidence: 99%
“…Furthermore, the conjugation chemistry is often difficult to control resulting in conjugates with ambiguities in composition. Also, the linker moiety can elicit strong B-cell responses 5,6 . Not surprisingly, preclinical and clinical studies with carbohydrate-protein conjugates have led to results of mixed merit.…”
Section: Online)mentioning
confidence: 99%
“…Tumor-associated saccharides are, however, of low antigenicity, because they are self-antigens and consequently tolerated by the immune system. In addition, foreign carrier proteins such as keyhole limpet hemocyanin (KLH) and bovine serum albumin (BSA) and the linker that attach the saccharides to the carrier protein can elicit strong B-cell responses, which may lead to the suppression of antibody responses against the carbohydrate epitope 5,6 . It is clear that the successful development of carbohydrate-based cancer vaccines requires novel strategies for the more efficient presentation of tumor-associated carbohydrate epitopes to the immune system, resulting in a more efficient class switch to IgG antibodies [7][8][9][10][11][12][13][14][15][16][17] .…”
mentioning
confidence: 99%
“…Since the identification of its epitope, MAb 2G12 has received significant attention as a template for HIV-1 vaccine development. Considerable effort has been directed at characterizing its oligosaccharide-binding profile (12)(13)(14)(15), and the generation of novel antigens in the form of synthetic oligomannoses (13,16,17) or short, synthetic glycopeptides (18)(19)(20). In an attempt to generate immunogens that elicit 2G12-like antibodies, we chose to isolate peptides that bind to 2G12 and inhibit antibody binding to the native oligomannose epitope on gp120, by screening a set of phage-displayed peptide libraries with MAb 2G12.…”
mentioning
confidence: 99%